Crisis Communication of Bigo Live Indonesia in Facing the Threat of Blocking: A Situational Crisis Communication Theory Analysis - Wuri Valendza Wijaya; Ratih Kurnia Hidayati; Ni Putu Limarandani (Advances in Community Services Research, 2026)
Purpose: This study examines the situational factors that escalated Bigo Live Indonesia's reputational crisis in 2024 and describes the crisis communication strategies the platform deployed in response to the Ministry of Communication and Information (Kominfo) 's threat to block. Research Method: A qualitative intrinsic case study was conducted using Situational Crisis Communication Theory (SCCT). Data comprised Bigo Live's official press release and eleven online news articles (CNNIndonesia.com, Detik.com, Kompas.com) published between August and September 2024, analyzed using NVivo 12 and verified through source triangulation. Results and Discussion: The crisis was preventable and was compounded by a history of recurring violations (a 2016 block and a 2024 non-compliance) and a poor reputation for relations. Bigo Live relied mainly on a rebuild strategy through compensation, supported by implicit deny-scapegoat, bolstering, and ethics-based tactics. Implications: The absence of an apology and the use of scapegoating weakened the response, suggesting that platforms facing regulatory sanction should pair technical compensation with explicit accountability. Originality: This study applies SCCT to a crisis on a live-streaming platform, driven simultaneously by regulatory pressure and a blocking threat. This multilayered context has rarely been examined in prior crisis communication research.